Bartalinia mellea - Sanchez, Romina Magali (2023)
Bartalinia mellea is a fungal species found only once, on the north slope of Cerro Tres Picos (in the south of Buenos Aires province) in 1988. This site is characterized by fragmented patches of natural grassland. The fungus was found on a shrubby plant, Mimosa rocae, which grows in grassland ecosystems over rocky outcrops; and it is suspected that it could be exclusively found with this plant. Despite the host plant being mostly distributed in Uruguay, and also occurring in one state of Brazil, the fungus is believed to be potentially restricted to a dry climate with long periods of insolation and very low temperatures in winter. So, it is suspected that the distribution of the fungus is restrict to the southern mountains of Buenos Aires province of Argentina. These mountains are of low height (up to 1,250 m asl) and the grassland ecosystems are mainly threatened by human activities such as tourist hiking, anthropogenic fire, introduction of invasive species and land use changes, resulting in its decline. There are not many potential sites for the species in the mountain ranges of Buenos Aires province (Argentina); and considering the extinction risk of M. rocae (VU in a national red list) it is parsimonious to assess the fungal species as declining. On the other hand, without clear information on its rate of decline and population size it is not possible to accurately quantify the extinction risk of B. mellea. Therefore, it is assessed as Data Deficient.